PHYSICIANS' KNOWLEDGE ABOUT PATIENTS' RELIGIOUS BELIEFS IN PEDIATRIC CARE - Lucas Zambusi Naufel; Maíra Terra Cunha Di Sarno; Maria Augusta Junqueira Alves
ABSTRACT Objective: To describe the knowledge of pediatricians and pediatric residents about the meaning of death according to the most prevalent religions in Brazil. Methods: A cross-sectional survey was conducted among pediatricians and pediatric residents at a tertiary-level children's hospital in the city of São Paulo, SP, Brazil, questioning about their knowledge and experience related to spiritual care and the most common religious beliefs among pediatric palliative care patients in Brazil. Results: 116 physicians answered the questionnaire, 98 (84.5%) considered themselves religious, defined as followers of any spiritual creed around the world, and 18 (15.5%) non-religious. Of the total, 97 (83.6%) considered themselves capable of dealing with the spiritual care of Catholic patients, 49 (42.2%) of Protestant patients and 92 (79.3%) of patients that follow Spiritism in the process of death. Religious doctors used less chaplaincy services than non-religious doctors (relative risk - RR 2.54; p=0.0432; confidence interval of 95% - 95%CI 1.21-5.34). Among the physicians, 111 (96%) believe that spirituality is beneficial in accepting the death process, responses were associated with the religiosity of the physicians (RR 1.18; p=0.0261; 95%CI 0.95-1.45). Also, 106 (91.4%) are unaware of the religion of their patients and the same number of participants consider pediatricians, in general, unprepared to deal with the spiritual aspect of death. These data are not associated with the participants' religiosity. Conclusions: Although most pediatricians and residents consider themselves able to deal with the most prevalent religions in Brazil and affirm that spirituality is beneficial during the death process, little importance is given to the spiritual identity of their patients, which could limit an appropriate approach to their death process.